The role of the psychologist in facing the cyberbullying among students of Sabha’s schools (Journal of Human Sciences, 2022)
This study aimed to know the roles of the psychologist in facing cyberbullying among school students and the sample of the study consisted of 30 psychologists from different basic and secondary education stages in Sebha city. As a matter of fact,the aforementioned sample was chosen randomly and after verifying the validity and reliability of the study tools, the study questions were answered.The study resulted in the following significant findings:-the roles of the psychologist in the face of cyberbullying among school students in the stages of education (basic /secondary) in Sebha city greatly differ.-there are no statistically significant differences due to the age variable among female psychologists in the face of cyberbullying.- there are no statistically significant differences due to the experience variable among female psychologists in the face of cyberbullying.